2022
DOI: 10.1021/acs.inorgchem.2c01876
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Displacement-Type Ferroelectric–Ferroelectric Phase Transition Compound [(NH3)(CH2)3(NH3)]2[InBr6]Br·H2O

Abstract: Ferroelectric materials have aroused the researchers' great interest due to their wide applications. Here, a displacement-type ferroelectric−ferroelectric phase transition material [(NH 3 )(CH 2 ) 3 (NH 3 )] 2 [InBr 6 ]Br•H 2 O (1) with T c = 143 K was successfully prepared. The ferroelectric phase transition is verified by the characterization techniques such as differential scanning calorimetry, single-crystal structure elucidation, dielectric and ferroelectric measurements. The single-crystal structure eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…2a, it can be observed that the distance between the propyl groups in the red dashed circle is significantly greater than that in 1-HTP , indicating that compound 1 undergoes a second-order shift phase transition. Based on the structural analysis of 1-LTP and 1-HTP , we can conclude that compound 1 undergoes a second-order shift ferroelectric–ferroelectric phase transition at 390 K, similar to the situation of [(NH 3 )(CH 2 ) 3 (NH 3 )] 2 [InBr 6 ]Br·H 2 O 39 and a pair of enantiomorphic diarylethene derivative ferroelectric crystals reported by Tang. 33…”
Section: Resultssupporting
confidence: 75%
“…2a, it can be observed that the distance between the propyl groups in the red dashed circle is significantly greater than that in 1-HTP , indicating that compound 1 undergoes a second-order shift phase transition. Based on the structural analysis of 1-LTP and 1-HTP , we can conclude that compound 1 undergoes a second-order shift ferroelectric–ferroelectric phase transition at 390 K, similar to the situation of [(NH 3 )(CH 2 ) 3 (NH 3 )] 2 [InBr 6 ]Br·H 2 O 39 and a pair of enantiomorphic diarylethene derivative ferroelectric crystals reported by Tang. 33…”
Section: Resultssupporting
confidence: 75%
“…Crystal structure analyses prove that the disorder–order change of the tetraalkylammonium cation induces phase transitions . In our previous work, we have found some inorganic–organic hybrid compounds with disorder–order or displacive phase transitions in the A n –3 [In III X n ] system. For instance, (C 4 H 10 N) 6 [InBr 6 ]­[InBr 4 ] 3 ·H 2 O exhibits a couple of thermal anomaly peaks at 232/227 K. The key factor for the phase transition is the disorder–order behavior of [InBr 4 ] − cations . Afterward, the displacement-type material [(NH 3 )­(CH 2 ) 3 (NH 3 )] 2 [InBr 6 ]­Br·H 2 O ( T p = 143 K) shows a ferroelectric–ferroelectric phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, the displacement-type material [(NH 3 )­(CH 2 ) 3 (NH 3 )] 2 [InBr 6 ]­Br·H 2 O ( T p = 143 K) shows a ferroelectric–ferroelectric phase transition. The displacive motion of organic cations provides the driving force for the phase transition . The studies described above indicate that A n –3 [In III X n ] offers an appropriate platform for the research of phase transition materials.…”
Section: Introductionmentioning
confidence: 99%